Pengembangan Scrapbook dalam Meningkatkan Motivasi Belajar Peserta Didik pada Pembelajaran IPAS Kelas III SD N Candirejo - Andriyani, Ika; Utaminingtyas, Siwi; Shinta Wardhani, Ratri (Universitas Muhammadiyah Magelang, 2026)
The development of scrapbooks in this study focused on supporting tools in science learning, which focused on increasing the learning motivation of third grade students at Candirejo Elementary School. By implementing the R&D framework, using five steps from the ADDIE model. Data were collected through validation instruments for experts, student response questionnaires, and learning motivation questionnaires. The findings of this study revealed that scrapbooks are classified as having a very high level of feasibility for application in science learning. This is based on the validation score of material experts reaching 95% and media experts at 88.75%, the percentage of results is in the